Towards A More Environmentally Friendly Nigeria: The Eco-Theatre for Children Initiative - Okoro, Lilian; Otonko, Juliana Sewuese (Social Sciences, Humanities and Education Journal (SHE Journal), 2024)
In Nigeria, despite numerous efforts to promote environmental safety, progress has been limited. Many young people, particularly children, need greater awareness of climate change's consequences, such as food scarcity. This paper examines the potential of eco-theatre as an effective tool for children's theatre to enhance environmental awareness among youth. By equipping children with knowledge about the importance of fostering a more eco-friendly Nigeria, children’s theatre plays a crucial role. Utilizing participatory action research and drama, this study addresses harmful environmental practices such as bush burning, deforestation, and bush meat hunting by highlighting their negative impacts and empowering children to advocate for environmental preservation. The paper showcases a children’s theatre production, "Bush Meat Makes You Bushy," developed from a three-day workshop, as a case study. The incorporation of the 'Catch them young' principle into eco-theatre aims to cultivate a generation of environmentally conscious children who can advocate for biodiversity conservation. Findings suggest that when children become environmental advocates, they can influence their parents and other adults. Given that children represent the future, they are ideal candidates for behavioral change initiatives. The paper concludes that eco-theatre for children can significantly aid in improving Nigeria's environmental condition, with eco-drama having the potential to enhance children's theatre experiences and boost their engagement with environmental issues.